IMPLEMENTASI KEBIJAKAN PENERTIBAN PEDAGANG PASAR DI KOTA MOJOKERTO - Tri Wahyuni, Agus; Wijaya, Dian; Suprapto (MAJAPAHIT POLICY, 2023)
In managing market levies, it is the government's task to regulate the collection process and manage resourcesincome obtained from traders from construction and facilities used. Department of Cooperatives, Small and Medium Enterprises,Industry and Trade in the city of Mojokerto is one of the agencies that provides (PAD). To increase regional incomeThe regional government of Mojokerto City has innovated to reduce the prevention of corruption by providing an E-Retribution application with the name RejoAngurimpi. The aim of this research is to determine the effect of the implementation of the Rejo Angurimpi policy on controlling market traders inMojokerto City. In principle, the implementation of a policy is a means for a policy to achieve its objectives. The methodused by researchers is a quantitative method using data analysis using the Shapiro Wilk normal test, validity and reliability and regression t test.The policy implementation regression coefficient (X) gets t count 5.193 > t table 2.035 and a significance value of 0.000 < 0.05 it can be concluded thatthe policy implementation variable (X) normally influences the trader control variable (Y). With a population of 269 traders,then using the Yamanane formula with a sampling error of 5%, the researcher obtained a sample of 35 respondents